Justice after Mao : the politics of historical truth in the People's Republic of China / edited by Daniel Leese, Amanda Shuman. - Leese, Daniel; Shuman, Amanda, 1980- (Cambridge University Press, 2023)
How can a dictatorship cope with the legacy of atrocities committed in its own name? This volume addresses the question of historical justice in post-Mao China through issues of property, rehabilitation, reconciliation, and memory. It provides a fresh perspective on Chinese history and politics, socialisms and transitional justice.